Adhesive composition, circuit connection material, and connection body

By using polyurethane resin, phenoxy resin, isocyanate radical polymerizable compound protected by blocking agent and phosphate radical polymerizable compound in the adhesive composition, the radical curing type bonding is solved by combining conductive particles. The problem of peeling agent under high temperature and high humidity conditions improves the bonding strength and peel resistance of the connector and ensures the reliability of the circuit connection.

CN119256059APending Publication Date: 2025-01-03RESONAC CORP
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202380041899.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-24
Filing Date
2023-05-09
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing radical curing adhesives are difficult to maintain connection reliability under high temperature and high humidity conditions, and peeling between circuit components and adhesive is prone to occur, affecting the stability and reliability of the connector.

Method used

A binder composition is adopted, including a thermoplastic resin, a free radical polymerizable compound and a free radical polymerization initiator, wherein the thermoplastic resin is a polyurethane resin and a phenoxy resin, and the free radical polymerizable compound has an isocyanate group protected by a blocking agent. The structure and phosphoric acid group are added to the binder composition to improve the storage stability of the binder and the peel resistance at high temperature and high humidity.

Benefits of technology

It is possible to achieve the possibility of adhesive surface peeling under high temperature and high humidity conditions, improve the bonding strength and peel resistance of the connector, and ensure the reliability and stability of the circuit connection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005145328480000091
    Figure BDA0005145328480000091
  • Figure BDA0005145328480000092
    Figure BDA0005145328480000092
  • Figure BDA0005145328480000093
    Figure BDA0005145328480000093
Patent Text Reader

Abstract

This adhesive composition contains (a) a thermoplastic resin, (b) a radical polymerizable compound, and (c) a radical polymerization initiator, in which the thermoplastic resin (a) contains (a-1) a polyurethane resin and (a-2) a phenoxy resin, and the radical polymerizable compound (b) contains (a-2) a phenoxy resin and the radical polymerization initiator (c) contains (a-3) a phenoxy resin and (a-3) a phenoxy resin. The adhesive composition contains (b-1) a radical polymerizable compound having a structure in which an isocyanate group is protected by an end-capping reagent and (b-2) a radical polymerizable compound having a phosphate group, and the content of the (b-2) radical polymerizable compound having a phosphate group is 1.6 mass% or less based on the total amount of the adhesive composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an adhesive composition, a circuit connection material and a connection body. Background Art

[0002] In semiconductor devices or liquid crystal display devices, various adhesive compositions have been used as circuit connection materials to bond various components in the devices. The adhesive compositions are required to have various properties including adhesion, heat resistance, and reliability under high temperature and high humidity conditions.

[0003] The adherend to be bonded has organic materials such as printed circuit boards, polyimide films, metals such as copper and aluminum, ITO, SiN, SiO 2 Therefore, the adhesive composition is designed according to each adherend.

[0004] As an adhesive composition for semiconductor elements or liquid crystal display elements, it is known to include a thermosetting resin composition of a thermosetting resin such as an epoxy resin that exhibits high adhesion and high reliability (for example, reference patent document 1). This adhesive composition usually contains an epoxy resin, a curing agent such as a phenolic resin that reacts with the epoxy resin, and a thermal potential catalyst that promotes the reaction of the epoxy resin and the curing agent. Among them, the thermal potential catalyst is an important factor in determining the curing temperature and the curing rate. Therefore, from the perspective of storage stability at room temperature and the curing rate during heating, various compounds are used as thermal potential catalysts. The adhesive composition is usually cured by heating at a temperature of 170 to 250° C. for 1 to 3 hours, thereby exerting the desired adhesion.

[0005] On the other hand, radical curing adhesives containing (meth)acrylate derivatives and peroxides have attracted much attention (for example, see Patent Document 2). In radical curing adhesives, since radicals as reactive species have abundant reactivity, they are advantageous in that they can be cured in a short time.

[0006] Previous technical literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Laid-Open No. 1-113480

[0009] Patent Document 2: International Publication No. 98 / 44067 Pamphlet Summary of the invention

[0010] Technical issues to be solved by the invention

[0011] In recent years, the market has been increasing its requirements for the reliability of panel quality such as liquid crystal display devices. Radical curing adhesives used as circuit connection materials are required to have sufficient storage stability and to maintain the connection reliability of the connection body even under harsh high temperature and high humidity conditions. Therefore, in order to improve the connection reliability of the connection body, the inventors of the present invention have conducted research on improving the bonding strength of the radical curing adhesive, and found the following problems.

[0012] The present inventors have made detailed observations on the connected bodies after the high temperature and high humidity test, and have found that in the connected bodies connected by the adhesive subjected to a storage treatment (for example, storage at 40°C for 3 days) in consideration of practical storage stability, peeling sometimes occurs between the circuit components and the cured product of the adhesive. The occurrence of peeling is sometimes not related to the adhesive strength, and if the peeling progresses further, it may lead to poor connection of the connected body, so peeling resistance is an important property for free radical curing adhesives.

[0013] Therefore, an object of the present invention is to provide an adhesive composition and a circuit connecting material that can achieve both storage stability and peeling resistance under high temperature and high humidity conditions, and a connected body that is unlikely to peel at the adhesive surface even under high temperature and high humidity conditions.

[0014] Means for solving technical problems

[0015] The contents of the present invention are as follows [1] to [8].

[0016] [1] An adhesive composition comprising (a) a thermoplastic resin, (b) a radical polymerizable compound, and (c) a radical polymerization initiator, wherein:

[0017] (a) The thermoplastic resin contains (a-1) a polyurethane resin and (a-2) a phenoxy resin,

[0018] (b) The radically polymerizable compound includes (b-1) a radically polymerizable compound having an isocyanate group protected by a blocking agent and (b-2) a radically polymerizable compound having a phosphoric acid group.

[0019] The content of the radically polymerizable compound (b-2) having a phosphoric acid group is 1.6% by mass or less based on the total amount of the adhesive composition.

[0020] [2] The adhesive composition according to [1] above, wherein the mass ratio of the (a-1) polyurethane resin to the (a-2) phenoxy resin is 8:2 to 2:8.

[0021] [3] The adhesive composition according to [1] or [2] above, wherein the (a-1) polyurethane resin is an ester urethane compound.

[0022] [4] The adhesive composition according to any one of [1] to [3] above, wherein the (b-1) radical polymerizable compound having a structure in which an isocyanate group is protected by a blocking agent is a (meth)acrylate compound having a pyrazole-blocked isocyanate group.

[0023] [5] A circuit connecting material comprising the adhesive composition according to any one of [1] to [4] above.

[0024] [6] The circuit connecting material according to [5] above, further comprising conductive particles.

[0025] [7] A connector comprising:

[0026] A first circuit component having a first circuit electrode formed on a main surface of a first circuit substrate;

[0027] A second circuit component having a second circuit electrode formed on a main surface of a second circuit substrate, wherein the second circuit electrode is arranged to face the first circuit electrode; and

[0028] a connecting component, disposed between the first circuit component and the second circuit component, and electrically connecting the first circuit component and the second circuit component,

[0029] The connecting member includes a cured product of the adhesive composition according to any one of [1] to [4] above.

[0030] [8] The connection body according to [7] above, wherein at least one of the first circuit substrate and the second circuit substrate is a glass substrate.

[0031] Effects of the Invention

[0032] According to the present invention, an adhesive composition and a circuit connecting material that can achieve both storage stability and peeling resistance under high temperature and high humidity conditions, and a connected body that is unlikely to peel on the adhesive surface even under high temperature and high humidity conditions can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a schematic cross-sectional view showing one embodiment of a film-like circuit connection material including the adhesive composition of the present embodiment.

[0034] Figure 2 This is a schematic cross-sectional view showing one embodiment of a connected body including a connecting member including a cured product of the adhesive composition according to the present embodiment.

[0035] Figure 3 This is a process diagram showing one embodiment of producing a connected body using the circuit connecting material of the present embodiment with a schematic cross-sectional view. DETAILED DESCRIPTION

[0036] In this specification, the numerical range represented by "~" indicates a range including the numerical values ​​recorded before and after "~" as the minimum value and the maximum value, respectively. In the numerical range recorded in stages in this specification, the upper limit or lower limit of the numerical range of a certain stage can also be replaced by the upper limit or lower limit of the numerical range of other stages. Moreover, in the numerical range recorded in this specification, the upper limit or lower limit of the numerical range can also be replaced by the value shown in the embodiment. Moreover, the upper limit and lower limit recorded individually can be combined arbitrarily. Moreover, in this specification, "(meth)acrylate" refers to at least one of acrylate and its corresponding methacrylate. The same is true in other similar expressions such as "(meth)acryloyl". Moreover, "(poly)" refers to both the case with the "poly" prefix and the case without the "poly" prefix. Moreover, "A or B" can include either A and B, or both. Moreover, the materials exemplified below can be used alone or in combination of two or more unless otherwise specified. When a plurality of substances corresponding to each component are present in the composition, the content of each component in the composition refers to the total amount of the plurality of substances present in the composition unless otherwise specified.

[0037] Below, depending on the situation, refer to the attached Figure 1 Embodiments of the present invention will be described in detail. However, the present disclosure is not limited to the following embodiments.

[0038] <Adhesive composition>

[0039] The adhesive composition of the present embodiment contains (a) a thermoplastic resin (hereinafter also referred to as "component (a)"), (b) a radical polymerizable compound (hereinafter also referred to as "component (b)"), and (c) a radical polymerization initiator (hereinafter also referred to as "component (c)").

[0040] Examples of the (a) thermoplastic resin include one or more resins selected from polyimide resins, polyamide resins, phenoxy resins, poly(meth)acrylic resins, polyester resins, polyurethane resins, polyester urethane resins, and polyvinyl butyral resins.

[0041] The lower limit of the weight average molecular weight of the thermoplastic resin may be 5000 or more, 10000 or more, or 25000 or more. If the weight average molecular weight of the thermoplastic resin is 5000 or more, the adhesive strength of the adhesive composition tends to be improved. On the other hand, the upper limit of the weight average molecular weight of the thermoplastic resin may be 400000 or less, 200000 or less, or 150000 or less. If the weight average molecular weight of the thermoplastic resin is 400000 or less, it tends to be easy to obtain good compatibility with other components and has a tendency to easily obtain the fluidity of the adhesive. From the above viewpoints, the weight average molecular weight of the thermoplastic resin is preferably 5000 to 400000, more preferably 5000 to 200000, further preferably 10000 to 150000, and particularly preferably 25000 to 150000.

[0042] The weight average molecular weight of the thermoplastic resin refers to a value measured by gel permeation chromatography (GPC) using a calibration curve based on standard polystyrene under the following conditions.

[0043] [GPC conditions]

[0044] Equipment used: Hitachi L-6000 model [Hitachi, Ltd.], column: Gelpackg GL-R420 + Gelpackg GL-R430 + Gelpackg GL-R440 (3 in total) [manufactured by Hitachi Chemical Company, Ltd.], eluent: tetrahydrofuran, measurement temperature: 40°C, flow rate: 1.75 ml / min, detector: L-3300RI [Hitachi, Ltd.]

[0045] As the thermoplastic resin, a rubber component may be used in order to relax stress and improve adhesiveness.

[0046] From the viewpoint of adhesive strength, film forming properties and fluidity of the adhesive composition, the total content of component (a) in the adhesive composition may be 20 to 80 parts by mass, 30 to 70 parts by mass, or 35 to 65 parts by mass relative to 100 parts by mass of the total amount of components (a) and (b).

[0047] From the viewpoint of balancing storage stability, peel resistance and adhesive strength under high temperature and high humidity conditions, the adhesive composition of the present embodiment may contain as the (a) component (a-1) polyurethane resin (hereinafter also referred to as the "(a-1) component") and the (a-2) phenoxy resin (hereinafter also referred to as the "(a-2) component".).

[0048] As the component (a-1), an organic compound having a carbamate group and an ester group (hereinafter also referred to as an "ester carbamate compound") can be used. The ester carbamate compound may have a carbamate group and an ester group in its main chain.

[0049] The ester urethane compound is obtained, for example, by the reaction of a polyester polyol with a diisocyanate. The ester urethane compound obtained by the reaction is generally referred to as a polyester urethane resin.

[0050] As the diisocyanate, aromatic, alicyclic or aliphatic diisocyanates such as 2,4-toluene diisocyanate (TDI), 4,4′-diphenylmethane diisocyanate (MDI), 1,6-hexamethylene diisocyanate (HDI) and isophorone diisocyanate (IPDI) can be preferably used.

[0051] Polyester polyols are obtained, for example, by the reaction of dicarboxylic acids and diols. As dicarboxylic acids, aromatic or aliphatic dicarboxylic acids such as terephthalic acid, isophthalic acid, adipic acid, and sebacic acid are preferred. As diols, glycols such as ethylene glycol, propylene glycol, 1,4-butanediol, hexanediol, neopentyl glycol, diethylene glycol, and triethylene glycol are preferred.

[0052] The glass transition temperature of the ester urethane compound is preferably 50° C. or higher. The glass transition temperature of the ester urethane compound can be adjusted to 50° C. or higher by appropriately adjusting the type, molecular weight, etc. of the polyester polyol or diisocyanate.

[0053] The ester urethane compound is preferably anionic. This further improves the adhesive strength. The anionic ester urethane compound is obtained by copolymerizing a diol or diamine having a sulfonic acid group or a carboxyl group in a side chain during the reaction of a polyester polyol and a diisocyanate.

[0054] The ester carbamate compound preferably has an aromatic group including a benzene ring or the like, or a cyclic aliphatic group including a cyclohexane ring or the like.

[0055] The ester urethane compound may be used in combination of two or more kinds. For example, a product obtained by reaction of an aromatic polyester polyol and an aliphatic diisocyanate and a product obtained by reaction of an aliphatic polyester polyol and an aromatic diisocyanate may be used in combination.

[0056] From the viewpoint of film formability, solubility in solvents and compatibility when formed into a film, the weight average molecular weight of the ester carbamate compound can be 5,000 to 100,000. From the viewpoint of balancing storage stability, peel resistance and adhesive strength under high temperature and high humidity conditions, the weight average molecular weight can be 5,000 to 400,000.

[0057] The ester urethane compound may have an epoxy group. When the adhesive composition contains the ester urethane compound having an epoxy group and an epoxy resin, the elastic modulus and heat resistance of the cured product of the circuit connecting material can be improved by the reaction between the epoxy resin and the ester urethane compound.

[0058] The component (a-1) can be used alone or in combination of two or more.

[0059] The weight average molecular weight of the phenoxy resin as the component (a-2) may be 10,000 or more, or 10,000 to 1,000,000.

[0060] The glass transition temperature of the phenoxy resin may be -50°C or higher, or 0 to 250°C.

[0061] The component (a-2) can be used alone or in combination of two or more.

[0062] From the viewpoint of achieving a balance between storage stability and peel resistance and adhesive strength under high temperature and high humidity conditions, the mass ratio of component (a-1) to component (a-2) may be 8:2 to 2:8, 7:3 to 3:7, or 6:4 to 4:6.

[0063] From the viewpoint of balancing storage stability, peel resistance and adhesive strength under high temperature and high humidity conditions, the total content of the adhesive composition of this embodiment, based on the total amount of the adhesive composition, can be 20 to 80 mass %, 20 to 70 mass % or 20 to 60 mass %.

[0064] From the viewpoint of balancing storage stability, peel resistance and adhesive strength under high temperature and high humidity conditions, the content of component (a-1) in the adhesive composition of this embodiment can be 5 to 50 parts by mass, 5 to 40 parts by mass or 5 to 30 parts by mass relative to 100 parts by mass of the total amount of components (a) and (b).

[0065] From the viewpoint of balancing storage stability, peel resistance and adhesive strength under high temperature and high humidity conditions, the content of component (a-2) in the adhesive composition of this embodiment can be 5 to 50 parts by mass, 5 to 40 parts by mass or 5 to 30 parts by mass relative to 100 parts by mass of the total amount of components (a) and (b).

[0066] From the viewpoint of balancing storage stability, peel resistance and adhesive strength under high temperature and high humidity conditions, the adhesive composition of the present embodiment may contain (b-1) a free radical polymerizing compound having a structure in which an isocyanate group is protected by a blocking agent (hereinafter also referred to as "(b-1) component") and (b-2) a free radical polymerizing compound having a phosphate group (hereinafter also referred to as "(b-2) component") as (b) a free radical polymerizing compound.

[0067] (b-1) Component may have a radical polymerizable unsaturated group. Examples of the radical polymerizable unsaturated group include a (meth)acryloyl group and a (meth)acryloyloxy group.

[0068] The component (b-1) can be synthesized by chemically blocking the isocyanate group of a compound having an isocyanate group and a (meth)acryloyloxy group with a blocking agent.

[0069] Examples of methods for producing a compound having an isocyanate group and a (meth)acryloyloxy group include a method of reacting a salt of (meth)acrylic acid and an amino alcohol ester with phosgene, a method of reacting isopropenyloxazoline with phosgene, and a method of dehydrochlorinating a 3-chloropropionate derivative having an isocyanate group, as described in JP-A-2006-232797.

[0070] The molecular weight of the compound having an isocyanate group and a (meth)acryloyloxy group may be 150 or more and less than 1,000.

[0071] In the compound having an isocyanate group and a (meth)acryloyloxy group, the number of the isocyanate group and the (meth)acryloyloxy group in the molecule is not particularly limited, but it is practical that the number of each is independently about 1 to 5.

[0072] Examples of the compound having an isocyanate group and a (meth)acryloyloxy group include 2-(meth)acryloyloxyethyl isocyanate, 2-(meth)acryloyloxymethyl isocyanate, 2-(meth)acryloyloxypropyl isocyanate, and 1,1-(bisacryloyloxymethyl)ethyl isocyanate.

[0073] Examples of the blocking agent include dimethylpyrazole, dimethyl malonate, diethyl malonate, methyl ethyl ketoxime and caprolactam. Since the dissociation temperature of the blocking agent can be controlled by the type of the blocking agent, these blocking agents can be used alone or in combination of two or more depending on the practical temperature.

[0074] The component (b-1) may be, for example, a compound obtained by blocking the compound having an isocyanate group and a (meth)acryloyloxy group using the blocking agent. Specific examples thereof include 2-(0-[1'-methylpropylideneamino]carboxyamino)ethyl (meth)acrylate and 2-([(3,5-dimethylpyrazolyl)carbonylamino])ethyl (meth)acrylate.

[0075] From the viewpoint of achieving a balance between storage stability and peel resistance and adhesive strength under high temperature and high humidity conditions, the component (b-1) may be a (meth)acrylate compound having a pyrazole-blocked isocyanate group such as 2-([(3,5-dimethylpyrazolyl)carbonylamino])ethyl (meth)acrylate.

[0076] The component (b-1) can be used alone or in combination of two or more.

[0077] From the viewpoint of balancing storage stability, peel resistance and adhesive strength under high temperature and high humidity conditions, the content of component (b-1) can be 1 to 25 parts by mass, 1 to 20 parts by mass, or 1 to 15 parts by mass, based on 100 parts by mass of the total amount of components (a) and (b).

[0078] Furthermore, from the viewpoint of balancing storage stability, peel resistance and adhesive strength under high temperature and high humidity conditions, the content of component (b-1) can be 1 to 50 parts by mass, 1 to 40 parts by mass, or 1 to 30 parts by mass, based on 100 parts by mass of the total amount of component (b).

[0079] Examples of the component (b-2) include compounds represented by the following formula (1), (2) or (3).

[0080]

[0081] In formula (1), R 5 represents a hydrogen atom or a methyl group, R 6 represents a (meth)acryloyloxy group, and w and x each independently represent an integer of 1 to 8. In addition, a plurality of R 5 , R 6 , w and x may be the same or different.

[0082]

[0083] In formula (2), R 7 represents a (meth)acryloyloxy group, and y and z each independently represent an integer of 1 to 8. A plurality of R in the same molecule 7 , y and z may be the same or different.

[0084]

[0085] In formula (3), R 8 represents a hydrogen atom or a methyl group, R 9 represents a (meth)acryloyloxy group, and b and c each independently represent an integer of 1 to 8. A plurality of R in the same molecule 8 and b may be the same or different.

[0086] Examples of the radical polymerizable compound having a phosphate group include phosphooxyethyl (meth)acrylate, phosphooxypropyl (meth)acrylate, acidic phosphooxy polyethylene glycol mono(meth)acrylate, acidic phosphooxy polyoxypropylene glycol mono(meth)acrylate, 2,2′-di(meth)acryloyloxy diethyl phosphate, EO (ethylene oxide)-modified phosphate di(meth)acrylate, phosphoric acid-modified epoxy (meth)acrylate, and vinyl phosphate.

[0087] The component (b-2) can be used alone or in combination of two or more.

[0088] From the viewpoint of balancing storage stability, peel resistance and adhesive strength under high temperature and high humidity conditions, the content of component (b-2) may be 1.6% by mass or less, 0.4 to 1.6% by mass, 0.5 to 1.6% by mass, or 1.0 to 1.6% by mass, based on the total amount of the adhesive composition (excluding conductive particles).

[0089] Furthermore, from the viewpoint of balancing storage stability, peel resistance and adhesive strength under high temperature and high humidity conditions, the content of component (b-2) can be 0.5 to 1.9 parts by mass, or 1.2 to 1.9 parts by mass, based on 100 parts by mass of the total amount of components (a) and (b).

[0090] Moreover, from the perspective of balancing storage stability and peel resistance and adhesive strength under high temperature and high humidity conditions, the content of component (b-2) can be 0.8 to 3.4 parts by mass, or 2.1 to 3.4 parts by mass, based on 100 parts by mass of the total amount of component (b).

[0091] The adhesive composition of this embodiment may include any other compound having a radical polymerizable functional group as (b) a radical polymerizable compound in addition to the above-mentioned components (b-1) and (b-2). The above-mentioned other compound may be, for example, any one of the monomers and oligomers of the compounds described later, or a compound obtained by using both.

[0092] As the above-mentioned other compounds, one or more multifunctional (meth)acrylate compounds having more than two (meth)acryloyloxy groups are preferred. As such (meth)acrylate compounds, for example, epoxy (meth)acrylate, urethane (meth)acrylate, polyether (meth)acrylate, polyester (meth)acrylate, trimethylolpropane tri(meth)acrylate, polyalkylene glycol di(meth)acrylate such as polyethylene glycol di(meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, neopentyl glycol di(meth)acrylate, dipentaerythritol hexa(meth)acrylate, isocyanuric acid-modified bifunctional (meth)acrylate, and isocyanuric acid-modified trifunctional (meth)acrylate can be cited. Examples of the epoxy (meth)acrylate include compounds obtained by introducing a (meth)acryloyloxy group into epoxy (meth)acrylate in which (meth)acrylic acid is added to two glycidyl groups of bisphenol fluorene diglycidyl ether, and compounds obtained by adding ethylene glycol and / or propylene glycol to two glycidyl groups of bisphenol fluorene diglycidyl ether. These compounds can be used alone or in combination of two or more.

[0093] In addition, the adhesive composition may contain a monofunctional (meth)acrylate compound as (b) a radical polymerizable compound for the purpose of adjusting fluidity, etc. Examples of the monofunctional (meth)acrylate compound include pentaerythritol (meth)acrylate, 2-cyanoethyl (meth)acrylate, cyclohexyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, 2-(2-ethoxyethoxy)ethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-hexyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, isobornyl (meth)acrylate, Isodecyl (meth)acrylate, isooctyl (meth)acrylate, n-undecyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, 2-(meth)acryloyloxyethyl phosphate, N,N-dimethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylate, a glycidyl group-containing (meth)acrylate obtained by reacting one glycidyl group of an epoxy resin having multiple glycidyl groups with (meth)acrylic acid, and (meth)acryloylmorpholine. These compounds can be used alone or in combination of two or more.

[0094] Furthermore, the adhesive composition may contain a compound having a radically polymerizable functional group such as an allyl group, a maleimide group, or a vinyl group as the (b) radically polymerizable compound for the purpose of improving the bridging rate or the like.

[0095] In addition, from the viewpoint of obtaining a balance between crosslink density and cure shrinkage, further reducing connection resistance, and improving connection reliability, the adhesive composition, as (b) a free radical polymerizable compound, may be included in a compound of polymerizable groups such as vinyl, allyl, (meth) acryloyl introduced into the end or side chain of thermoplastic resins such as acrylic resins, phenoxy resins, and polyurethane resins. At this time, from the viewpoint of excellent balance between crosslink density and cure shrinkage, the weight average molecular weight of the above-mentioned compound can be more than 3000, more than 5000, or more than 10,000. In addition, from the viewpoint of excellent compatibility with other components, the weight average molecular weight of the above-mentioned compound can be less than 1,000,000, less than 500,000, or less than 250,000. In addition, the weight average molecular weight of the above-mentioned compound refers to the value measured by the calibration curve of standard polystyrene by gel permeation chromatography (GPC) according to the conditions described in the embodiment.

[0096] The compound may be an ester urethane compound containing a radically polymerizable unsaturated double bond or a radically polymerizable unsaturated double bond and an epoxy resin. In this case, the elastic modulus or heat resistance of the cured product of the circuit connecting material can be improved.

[0097] As the above-mentioned other compounds, when used in combination with the components (b-1) and (b-2), from the viewpoint of achieving a balance between crosslinking density and curing shrinkage, further reducing connection resistance, and improving peel resistance and adhesive strength under high temperature and high humidity conditions, (poly)urethane (meth)acrylate compounds can be used. The (poly)urethane (meth)acrylate compound can be an ester urethane compound having a (meth)acryloyl group. In this case, the elastic modulus or heat resistance of the cured product of the circuit connection material can be improved.

[0098] The content of the (poly)urethane (meth)acrylate compound may be 30 to 90% by mass or 30 to 80% by mass based on the total mass of the component (b).

[0099] Furthermore, the content of the (poly)urethane (meth)acrylate compound may be 50 to 90 parts by mass or 50 to 80 parts by mass based on 100 parts by mass of the total amount of the components (b-1) and (b-2).

[0100] The total content of the component (b) in the adhesive composition may be 20 to 80 parts by mass, 30 to 70 parts by mass, or 35 to 65 parts by mass based on 100 parts by mass of the total amount of the components (a) and (b).

[0101] (c) The radical polymerization initiator can be arbitrarily selected from compounds such as peroxides and azo compounds. From the viewpoints of stability, reactivity and compatibility, peroxides having a 1-minute half-life temperature of 90 to 175°C and a molecular weight of 180 to 1000 are preferred. "1-minute half-life temperature" refers to the temperature at which the half-life of the peroxide is 1 minute. "Half-life" refers to the time until the concentration of a compound decreases to half of the initial value at a specified temperature.

[0102] The radical polymerization initiator is, for example, 1,1,3,3-tetramethylbutyl peroxyneodecanoate, di(4-tert-butylcyclohexyl)peroxydicarbonate, di(2-ethylhexyl)peroxydicarbonate, cumyl peroxyneodecanoate, 1,1,3,3-tetramethylbutyl peroxyneodecanoate, dilauroyl peroxide, 1-cyclohexyl-1-methylethyl peroxyneodecanoate, tert-hexyl peroxyneodecanoate, tert-butyl peroxyneodecanoate, tert-butyl peroxypivalate, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, 2,5 -Dimethyl-2,5-di(2-ethylhexanoylperoxy)hexane, tert-hexyl peroxy-2-ethylhexanoate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxy neoheptanoate, tert-amyl peroxy-2-ethylhexanoate, di-tert-butyl peroxyhexahydroterephthalate, tert-amyl peroxy-3,5,5-trimethylhexanoate, 3-hydroxy-1,1-dimethylbutyl peroxy neodecanoate, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, tert-amyl peroxy neodecanoate, tert-amyl peroxy-2-ethylhexanoate, 3-methylbenzene Formyl peroxide, 4-methylbenzoyl peroxide, di(3-methylbenzoyl) peroxide, dibenzoyl peroxide, di(4-methylbenzoyl) peroxide, 2,2'-azobis-2,4-dimethylvaleronitrile, 1,1'-azobis(1-acetoxy-1-phenylethane), 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), dimethyl-2,2'-azobisisobutyronitrile, 4,4'-azobis(4-cyanovaleric acid), 1,1'-azobis(1-cyclohexanecarbonitrile), tert-hexyl peroxide isopropyl monoisopropyl Carbonate, tert-butyl peroxymaleic acid, tert-butyl peroxy-3,5,5-trimethylhexanoate, tert-butyl peroxylaurate, 2,5-dimethyl-2,5-di(3-methylbenzoylperoxy)hexane, tert-butyl peroxy-2-ethylhexyl monocarbonate, tert-hexyl peroxybenzoate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, tert-butyl peroxybenzoate, dibutyl peroxytrimethyladipate, tert-amyl peroxyoctanoate, tert-amyl peroxyisononanoate and tert-amyl peroxybenzoate.

[0103] The content of the radical polymerization initiator is preferably 1 to 15 parts by mass, more preferably 2.5 to 10 parts by mass, and even more preferably 3 to 8 parts by mass, based on 100 parts by mass of the total amount of the components (a) and (b).

[0104] The adhesive composition of the present embodiment may contain a silane coupling agent. As the silane coupling agent, a compound represented by the following formula (4) can be used.

[0105]

[0106] In formula (4), R 1 , R 2 and R 3 R each independently represents a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, an alkoxy group having 1 to 5 carbon atoms, an alkoxycarbonyl group having 1 to 5 carbon atoms, or an aryl group. 1 , R 2 and R 3 At least one of R is an alkoxy group. 4 represents a (meth)acryloyl group, a (meth)acryloyloxy group, a vinyl group, an isocyanate group, an imidazole group, a mercapto group, an amino group which may be substituted with an aminoalkyl group, a methylamino group, a dimethylamino group, a benzylamino group, a phenylamino group, a cyclohexylamino group, a morpholino group, a piperazinyl group, a ureido group, a glycidyl group or a glycidoxy group. a represents an integer of 0 to 10.

[0107] As the coupling agent in formula (4), for example, vinyl trimethoxysilane, vinyl triethoxysilane, 3-glycidyloxypropyl trimethoxysilane, 3-glycidyloxypropyl methyl diethoxysilane, 3-(methyl)acryloxypropyl methyl dimethoxysilane, 3-(methyl)acryloxypropyl trimethoxysilane, 3-(methyl)acryloxypropyl methyl diethoxysilane, 3-(methyl)acryloxypropyl triethoxysilane, N-2-(aminoethyl)-3-aminopropyl methyl dimethoxysilane, N-phenyl-3-aminopropyl trimethoxysilane, 3-ureidopropyl triethoxysilane, 3-mercaptopropyl trimethoxysilane and 3-isocyanate propyl triethoxysilane can be mentioned. These compounds can be used alone or in combination of two or more.

[0108] The content of the silane coupling agent may be 0.1 to 10 parts by mass, or 0.25 to 5 parts by mass, based on 100 parts by mass of the total amount of the components (a) and (b).

[0109] The adhesive composition of the present embodiment can contain a filler. As a filler, insulating organic or inorganic particles can be cited. As inorganic particles, for example, in addition to metal oxide particles such as silica particles, alumina particles, silica-alumina particles, titanium dioxide particles, and zirconium oxide particles, nitride particles can also be cited. As organic particles, for example, silicone particles, methacrylate-butadiene-styrene particles, acrylic acid-silicone particles, polyamide particles, polyimide particles, etc. can be cited. These particles can have a uniform structure or a core-shell structure.

[0110] From the viewpoint of maintaining electrical connection between opposing electrodes and improving fluidity of the adhesive composition, the content of the filler may be 5 to 30 parts by mass, or 7.5 to 20 parts by mass, based on 100 parts by mass of the total amount of the components (a) and (b).

[0111] In addition, the adhesive composition of the present embodiment may contain other additives such as a softener, an accelerator, an anti-degradation agent, a colorant, a flame retardant, a thixotropic agent, and a polymerization inhibitor. Examples of the polymerization inhibitor include hydroquinone, methyl ether hydroquinones, TEMPO (e.g., 4-benzoyloxy-2,2,6,6-tetramethylpiperidinyloxy free radical, 2,2,6,6-tetramethylpiperidinyloxy free radical), and hindered amines.

[0112] When the adhesive composition of the present embodiment is liquid at room temperature (25° C.), it can be used as a paste adhesive. When the adhesive composition is solid at room temperature, it can be heated for use, or it can be used by adding a solvent to make it into a paste. The solvent used for the paste is not particularly limited as long as it is substantially non-reactive with the adhesive composition (including additives) and can fully dissolve the adhesive composition.

[0113] The adhesive composition of this embodiment can also be formed into a film and used as a film adhesive. The film adhesive can be obtained, for example, by applying a solution obtained by adding a solvent or the like to the adhesive composition as needed on a releasable support such as a fluororesin film, a polyethylene terephthalate film, or a release paper, and removing the solvent or the like. From the viewpoint of operation, the film adhesive is more convenient.

[0114] <Circuit connection materials>

[0115] The circuit connecting material of the present embodiment includes the adhesive composition of the present embodiment described above.

[0116] The circuit connecting material of this embodiment may further contain conductive particles. The circuit connecting material containing conductive particles can be particularly preferably used as an anisotropic conductive adhesive.

[0117] As conductive particles, for example, metal particles such as Au, Ag, Pd, Ni, Cu, solder, and carbon particles can be cited. In addition, the conductive particles can be composite particles having a core particle formed of a non-conductive material such as glass, ceramics, and plastics and a conductive layer of metal, metal particles, carbon, etc. covering the core particle. The metal particles can be copper particles and particles having a silver layer covering the copper particles. The core particles of the composite particles are preferably plastic particles.

[0118] Since the composite particles using the above-mentioned plastic particles as core particles have the deformability to deform by heating and pressurizing, when bonding circuit components together, the contact area between the circuit electrodes of the circuit components and the conductive particles can be increased. Therefore, according to the circuit connection material containing these composite particles as conductive particles, a connection body with better connection reliability can be obtained.

[0119] The circuit connection material may contain insulating coated conductive particles, which have the above conductive particles and an insulating layer or insulating particles covering at least a portion of the surface thereof. The insulating layer may be provided by a method such as hybridization. The insulating layer or insulating particles are formed of insulating materials such as polymer resins. By using such insulating coated conductive particles, it is difficult for short circuits caused by adjacent conductive particles to occur.

[0120] From the viewpoint of obtaining good dispersibility and conductivity, the average particle diameter of the conductive particles is preferably 1 to 18 μm.

[0121] From the perspective of ensuring conductivity and preventing short circuits between circuit electrodes, the content of conductive particles can be 0.1 to 30% by volume, 0.1 to 10% by volume, or 0.5 to 7.5% by volume, based on the total volume of the circuit connection material. The content (volume %) of conductive particles is determined based on the volume of each component and conductive particle constituting the adhesive composition before curing at 23°C. The volume of each component and conductive particle can be obtained by converting the mass into volume using specific gravity. It is also possible to put an appropriate solvent (water, alcohol, etc.) that does not dissolve or swell the component to be measured and can fully wet the component into a measuring cylinder, etc., introduce the component to be measured therein, and obtain the increased volume as the volume of the component.

[0122] When the circuit connection material is liquid at room temperature (25°C), it can be used as a paste circuit connection material. When the adhesive composition is solid at room temperature, it can be heated for use or can be used by adding a solvent to make it paste-like. There is no particular limitation on the solvent used for the paste-like solvent as long as it is substantially non-reactive with the adhesive composition (including additives) and can fully dissolve the adhesive composition.

[0123] The circuit connection material of this embodiment can also be formed into a film and used as a film-shaped circuit connection material. The film-shaped circuit connection material can be obtained, for example, by adding a solvent or the like to a mixture of an adhesive composition and conductive particles as required, applying the obtained solution to a removable support such as a fluororesin film, a polyethylene terephthalate film, or a release paper, and removing the solvent or the like.

[0124] Figure 1 This is a schematic cross-sectional view showing one embodiment of a film-like circuit connection material including the adhesive composition of the present embodiment. Figure 1 The laminated film 100 shown has a support 8 and a film-like circuit connection material 40 laminated on the support 8 in a removable manner. The circuit connection material 40 is composed of an insulating adhesive layer 5 and conductive particles 7 dispersed in the insulating adhesive layer 5. The insulating adhesive layer 5 is composed of the above-mentioned adhesive composition. According to the circuit connection material, it is easy to handle, can be easily set on the adherend, and can be easily connected. The circuit connection material can have a multilayer structure formed by two or more layers. When the film-like circuit connection material contains conductive particles, the film-like circuit connection material can be suitably used as an anisotropic conductive film.

[0125] According to the adhesive composition or circuit connection material of the present embodiment, usually, it is possible to use heating and pressurization to make the adherends bonded to each other. The heating temperature is preferably 100-250°C. The pressure is not particularly limited as long as it does not damage the adherend, and is usually preferably 0.1-10MPa. These heating and pressurization are preferably carried out in the range of 0.5-120 seconds. According to the adhesive composition or circuit connection material of the present embodiment, for example, it is possible to heat and pressurize the adherends fully to each other under the conditions of 140°C and 3MPa, even a short time of 5 seconds of heating and pressurization.

[0126] The adhesive composition or circuit connection material of the present embodiment can be used as an adhesive for different types of adherends having different thermal expansion coefficients. Specifically, the adhesive composition or circuit connection material of the present embodiment can be used as a circuit connection material such as silver paste and silver film, an elastomer for CSP, a bottom filling material for CSP, an adhesive material for semiconductor elements such as LOC tape, in addition to anisotropic conductive adhesives.

[0127] Hereinafter, an example of manufacturing a connected body by connecting circuit components including a circuit substrate and circuit electrodes formed on the main surface of the circuit substrate as adherends using the circuit connecting material of the present embodiment as an anisotropic conductive film will be described.

[0128] Figure 2 This is a schematic cross-sectional view showing one embodiment of a connected body including a connecting member formed of a cured product of the adhesive composition of the present embodiment. Figure 2 The illustrated connection body 1 includes a first circuit member 20 and a second circuit member 30 disposed opposite to each other. A connection member 10 is provided between the first circuit member 20 and the second circuit member 30 to bond and connect them.

[0129] The first circuit member 20 includes a first circuit substrate 21 and a first circuit electrode 22 formed on a principal surface 21a of the first circuit substrate 21. An insulating layer may be formed on the principal surface 21a of the first circuit substrate 21.

[0130] The second circuit member 30 includes a second circuit substrate 31 and a second circuit electrode 32 formed on a principal surface 31a of the second circuit substrate 31. An insulating layer may be formed on the principal surface 31a of the second circuit substrate 31.

[0131] The first circuit component 20 and the second circuit component 30 are not particularly limited as long as they have circuit electrodes that need to be electrically connected. Examples of the first circuit substrate 21 and the second circuit substrate 31 include substrates made of inorganic materials such as semiconductors, glass, and ceramics, substrates made of organic materials such as polyimide and polycarbonate, and substrates containing inorganic and organic materials such as glass / epoxy. The first circuit substrate 21 may be a glass substrate, and the second circuit substrate 31 may be a flexible substrate (preferably a resin film such as a polyimide film).

[0132] Specific examples of the circuit components to be connected include glass or plastic substrates with electrodes such as ITO (indiumtin oxide) films for liquid crystal displays, printed circuit boards, ceramic circuit boards, flexible circuit boards, semiconductor silicon chips, etc. These can be used in combination as needed. Thus, the circuit connection material according to this embodiment can be used to bond circuit components with various surface states, such as those made of metals such as copper and aluminum, ITO, silicon nitride (SiN x ), silicon dioxide (SiO 2 ) and other inorganic materials.

[0133] For example, when one circuit component is a solar cell unit having electrodes such as a finger electrode and a busbar electrode, and another circuit component is a tab wire, the connection obtained by connecting them is a solar cell module having a solar cell unit, a tab wire and a connection component (a cured product of an adhesive composition) bonding them together.

[0134] The connecting component 10 includes a cured product of the adhesive composition of the present embodiment. The connecting component 10 contains an insulating layer 11 and conductive particles 7 dispersed in the insulating layer 11. The conductive particles 7 are not only arranged between the first circuit electrode 22 and the second circuit electrode 32 facing each other, but also arranged between the main surfaces 21a and 31a. The first circuit electrode 22 and the second circuit electrode 32 are electrically connected via the conductive particles 7, thereby sufficiently reducing the connection resistance between the first circuit electrode 22 and the second circuit electrode 32. Therefore, the flow of current between the first circuit electrode 22 and the second circuit electrode 32 can be smooth, and the function of the circuit can be fully exerted. When the connecting component does not contain conductive particles, the first circuit electrode 22 and the second circuit electrode 32 are electrically connected by contact.

[0135] Since the connecting component 10 is formed of a cured product of the adhesive composition of the present embodiment, the bonding strength of the connecting component 10 to the first circuit component 20 and the second circuit component 30 is sufficiently high, and the peeling resistance of the connecting component 10 is also excellent. Furthermore, even after a reliability test (high temperature and high humidity test), peeling is not likely to occur, and a decrease in bonding strength and an increase in connection resistance can be sufficiently suppressed.

[0136] An example of a connector can be manufactured by the following method, which comprises: a process of arranging a pair of circuit components having circuit electrodes and arranged opposite to each other in a manner of sandwiching a film-like circuit connecting material in the middle; and a process (formal connection process) of pressurizing and heating the pair of circuit components and the circuit connecting material along the thickness direction of the circuit connecting material to cure them, thereby bonding the pair of circuit components via a cured product of the adhesive composition.

[0137] Figure 3 This is a schematic cross-sectional view showing a process diagram of an embodiment of manufacturing a connection body using the circuit connection material of this embodiment. Figure 3 As shown in (a), the film-like circuit connection material 40 is placed on the main surface of the first circuit electrode 22 side of the first circuit component 20. In the case where the film-like circuit connection material 40 is arranged on the above-mentioned support body, the laminated body of the film-like circuit connection material and the support body is placed on the circuit component in the direction that the film-like circuit connection material 40 is located on the side of the first circuit component 20. Since the film-like circuit connection material 40 is in a film shape, it is easy to handle. Therefore, the film-like circuit connection material 40 can be easily sandwiched between the first circuit component 20 and the second circuit component 30, and the connection operation of the first circuit component 20 and the second circuit component 30 can be easily performed.

[0138] The film-like circuit connection material 40 is the above-mentioned circuit connection material formed into a film, and has conductive particles 7 and an insulating adhesive layer 5. Even in the case where the circuit connection material does not contain conductive particles, it can be used as a circuit connection material that electrically connects circuit electrodes to each other by directly connecting them. The circuit connection material that does not contain conductive particles is sometimes also called NCF (Non-Conductive-FILM: non-conductive film) or NCP (Non-Conductive-Paste: non-conductive paste). In the case where the circuit connection material has conductive particles, the circuit connection material using it is sometimes also called ACF (Anisotropic Conductive Film: anisotropic conductive film) or ACP (Anisotropic Conductive Paste: anisotropic conductive paste).

[0139] The thickness of the film-like circuit connection material 40 is preferably 10 to 50 μm. If the thickness of the film-like circuit connection material 40 is 10 μm or more, there is a tendency that the first circuit electrode 22 and the second circuit electrode 32 are easily filled with adhesive. If the thickness of the film-like circuit connection material is 50 μm or less, the adhesive composition between the first circuit electrode 22 and the second circuit electrode 32 can be sufficiently excluded, and the conduction between the first circuit electrode 22 and the second circuit electrode 32 can be easily ensured.

[0140] like Figure 3 As shown in FIG. 2A , the film-like circuit connecting material 40 is temporarily connected to the first circuit member 20 (see FIG. 2B ) by applying pressures A and B in the thickness direction of the film-like circuit connecting material 40. Figure 3(b). At this time, heating and pressurization may be performed. However, the heating temperature is set to a temperature at which the adhesive composition in the film-like circuit connection material 40 does not cure, that is, a temperature sufficiently lower than the temperature at which the radical polymerization initiator rapidly generates free radicals.

[0141] Then, if Figure 3 As shown in (c), the second circuit component 30 is placed on the film-like circuit connection material 40 in a direction in which the second circuit electrode is located on the side of the first circuit component 20. When the film-like circuit connection material 40 is provided on a support, the second circuit component 30 is placed on the film-like circuit connection material 40 after peeling off the support.

[0142] Then, the film-like circuit connection material 40 is heated while applying pressures A and B in the thickness direction thereof. The heating temperature at this time is set to a temperature at which the radical polymerization initiator sufficiently generates free radicals. Thus, free radicals are generated from the radical polymerization initiator, and polymerization of the radical polymerizable compound begins. By formal connection, a Figure 2 By heating the film-like circuit connection material 40, the insulating adhesive is cured to form the insulating layer 11 in a state where the distance between the first circuit electrode 22 and the second circuit electrode 32 is sufficiently reduced. As a result, the first circuit component 20 and the second circuit component 30 are firmly connected via the connection component 10 including the insulating layer 11.

[0143] The formal connection is preferably carried out under the conditions of a heating temperature of 100 to 250° C., a pressure of 0.1 to 10 MPa, and a pressing time of 0.5 to 120 seconds. These conditions are appropriately selected according to the application, adhesive composition, and circuit components. According to the circuit connection material of this embodiment, a connection body with sufficient reliability can be obtained even under low temperature conditions below 140° C. After the formal connection, post-curing can be performed as needed.

[0144] Example

[0145] Hereinafter, the present invention will be described in more detail using examples, but the present invention is not limited to the examples.

[0146] <Synthesis of ester carbamate compound EU1>

[0147] 48 parts by mass of isophthalic acid and 37 parts by mass of neopentyl glycol were put into a stainless steel autoclave with a heater equipped with a stirrer, a thermometer, a capacitor, a vacuum generator, and a nitrogen inlet pipe, and 0.02 parts by mass of tetrabutoxy titanate as a catalyst was further put in. Then, the temperature was raised to 220°C under a nitrogen flow, and stirred directly for 8 hours. After that, the pressure was reduced to atmospheric pressure (760 mmHg) and cooled to room temperature. Thus, a white precipitate was precipitated. Then, the white precipitate was taken out, washed with water, and vacuum dried to obtain a polyester polyol. After the obtained polyester polyol was fully dried, it was dissolved in MEK (methyl ethyl ketone) and put into a four-necked flask equipped with a stirrer, a dropping funnel, a reflux cooler and a nitrogen inlet pipe. Furthermore, as a catalyst, 0.05 parts by mass of dibutyltin dilaurate was added based on 100 parts by mass of the polyester polyol, and 50 parts by mass of 4,4′-diphenylmethane diisocyanate was dissolved in MEK based on 100 parts by mass of the polyester polyol and added using a dropping funnel, and the mixture was stirred at 80° C. for 4 hours, thereby obtaining the target ester carbamate compound EU1.

[0148] <Synthesis of polyurethane acrylate compound UA1>

[0149] In a 2-liter four-necked flask equipped with a thermometer, a stirrer, an inert gas inlet and a reflux cooler, 4000 parts by mass of polycarbonate diol (manufactured by Aldrich, number average molecular weight Mn = 2000), 238 parts by mass of 2-hydroxyethyl acrylate, 0.49 parts by mass of hydroquinone monomethyl ether, and 4.9 parts by mass of a tin-based catalyst were added to prepare a reaction solution. 666 parts by mass of isophorone diisocyanate (IPDI) were uniformly added dropwise to the reaction solution heated to 70°C over 3 hours to react. After the addition was completed, the reaction was continued for 15 hours, and the reaction was terminated when the NCO content became 0.2% by mass by a potentiometric automatic titrator (trade name AT-510, manufactured by KYOTO ELECTRONICS MANUFACTURING CO., LTD.), and a polyurethane acrylate compound UA1 was obtained. As a result of analysis by GPC, the weight average molecular weight of the polyurethane acrylate compound UA1 was 8500 (standard polystyrene conversion value). In addition, the analysis by GPC was performed under the conditions shown in Table 1 below.

[0150] [Table 1]

[0151]

[0152] <Production of conductive particles>

[0153] A nickel layer having a thickness of 0.2 μm was formed on the surface of the polystyrene particles, and a gold layer having a thickness of 0.04 μm was further formed on the outer side of the nickel layer. In this manner, conductive particles having an average particle diameter of 4 μm were produced.

[0154] <Manufacturing of circuit connection materials>

[0155] The raw materials shown in Table 2 were mixed in the mass ratio shown in Table 2 to obtain an adhesive composition. The conductive particles were dispersed therein at a ratio of 1.5% by volume to obtain a coating solution for forming a film-like circuit connection material. The coating solution was applied to a polyethylene terephthalate (PET) film having a thickness of 50 μm using a coating device. The coating film was hot-air dried at 70° C. for 10 minutes to form a film-like circuit connection material having a thickness of 18 μm.

[0156] Each numerical value shown in Table 2 represents the mass part of the solid content. In addition, the specific substance of each raw material described in Table 2 is as follows.

[0157] Polyurethane resin: Ester urethane compound EU1 synthesized as described above,

[0158] Phenoxy resin: a 40 mass % solution prepared by dissolving 40 g of PKHC (manufactured by Union Carbide Corporation, trade name: average molecular weight 45000) in 60 g of methyl ethyl ketone,

[0159] Polyurethane acrylate compound: polyurethane acrylate compound UA1 synthesized as described above,

[0160] Radical polymerizable compound A: 2-(0-[1'-methylpropylideneamino]carboxyamino)ethyl methacrylate,

[0161] Radical polymerizable compound B: 2-([(3,5-dimethylpyrazolyl)carbonylamino])ethyl methacrylate,

[0162] Radical polymerizable compound C: monofunctional acrylate compound (trade name Alix CHA, manufactured by TOAGOSEICO., LTD.: cyclohexyl acrylate),

[0163] Phosphate ester: 2-methacryloyloxyethyl acid phosphate (trade name: LIGHT ESTERP-2M, manufactured by KYOEISHA CHEMICAL Co., LTD.),

[0164] Silane coupling agent: 3-methacryloxypropyltrimethoxysilane (trade name KBM-503, manufactured by Shin-Etsu Chemical Co., Ltd.),

[0165] Peroxide: lauroyl peroxide (trade name Parroyl L, manufactured by NOF CORPORATION: molecular weight 398.6),

[0166] Inorganic fine particles: A 10% by mass dispersion prepared by dispersing 10 g of silica particles (trade name: R104, manufactured by Nippon AEROSIL Co., Ltd.) in a mixed solvent of 45 g of toluene and 45 g of ethyl acetate.

[0167] <Production of Connectors>

[0168] Using the above-mentioned film-like circuit connection material, a flexible circuit board (FPC) having 2200 copper circuits with a line width of 75μm, a spacing of 150μm and a thickness of 18μm was connected to an ITO substrate (thickness 1.1mm, surface resistance 20Ω / □) having a glass substrate and a thin layer of indium oxide (ITO) with a thickness of 0.2μm formed on the glass substrate. Using a thermocompression bonding device (heating method: constant temperature type, manufactured by TORAY ENGINEERING Co., Ltd.), the connection was made by heating and pressing at 140°C and 3MPa for 5 seconds. Thus, a connection body in which the FPC and the ITO substrate were connected by a cured product of the circuit connection material on a width of 1.5mm was produced.

[0169] <Measurement of Adhesion Strength>

[0170] The bonding strength of the obtained connection body was measured by the 90 degree peeling method according to JIS-Z0237. As a measuring device for the bonding strength, Tensilon UTM-4 (manufactured by TOYO BALDWIN K.K., trade name, peeling strength 50 mm / min, 25°C) was used. In addition, the bonding strength was measured after the connection body was kept in a constant temperature and humidity chamber at 85°C and 85% RH for 250 hours.

[0171] <Evaluation of peeling resistance>

[0172] After the connection body prepared in the same manner as above was kept in a constant temperature and humidity chamber at 85°C and 85%RH for 250 hours, the interface between the electrode portion of the glass substrate and the cured product of the circuit connection material was observed from the glass substrate side using a microscope (manufactured by Nikon Corporation, ECLIPSE L200), and the peeling state was evaluated in 5 stages. The proportion of the peeled portion from the glass substrate in the entire area of ​​the cured product of the circuit connection material was calculated, and the proportion of the peeled portion was less than 5% of the entire area, and was set to "5", the proportion of the peeled portion was 5% or more and less than 10% of the entire area, and was set to "4", the proportion of the peeled portion was 10% or more and less than 30% of the entire area, and was set to "3", the proportion of the peeled portion was 30% or more and less than 50% of the entire area, and was set to "2", and the proportion of the peeled portion was 50% or more of the entire area, and was set to "1".

[0173] <Evaluation of storage stability (after storage treatment)>

[0174] Using the film-like circuit connecting material treated at 40° C. for 3 days, a connection body was produced by the same method as above, and the adhesive strength was measured and the peeling resistance was evaluated by the above methods.

[0175] [Table 2]

[0176]

[0177] Explanation of symbols

[0178] 1-connector, 5-insulating adhesive layer, 7-conductive particles, 8-support, 10-connecting component, 11-insulating layer, 20-first circuit component, 21-first circuit substrate, 21a-main surface, 22-first circuit electrode, 30-second circuit component, 31-second circuit substrate, 31a-main surface, 32-second circuit electrode, 40-film circuit connecting material, 100-laminated film.

Claims

1. An adhesive composition comprising (a) a thermoplastic resin, (b) a radical polymerizable compound, and (c) a radical polymerization initiator, wherein: The (a) thermoplastic resin includes (a-1) a polyurethane resin and (a-2) a phenoxy resin. The (b) radical polymerizable compound includes (b-1) a radical polymerizable compound having an isocyanate group protected by a blocking agent and (b-2) a radical polymerizable compound having a phosphoric acid group. The content of the (b-2) radically polymerizable compound having a phosphate group is 1.6% by mass or less based on the total amount of the adhesive composition.

2. The adhesive composition according to claim 1, wherein The mass ratio of the (a-1) polyurethane resin to the (a-2) phenoxy resin is 8:2 to 2:

8.

3. The adhesive composition according to claim 1 or 2, wherein: The (a-1) polyurethane resin is an ester urethane compound.

4. The adhesive composition according to any one of claims 1 to 3, wherein The (b-1) radical polymerizable compound having a structure in which an isocyanate group is protected by a blocking agent is a (meth)acrylate compound having a pyrazole-blocked isocyanate group. 5 . A circuit connecting material comprising the adhesive composition according to claim 1 . The circuit connecting material according to claim 5 , further comprising conductive particles.

7. A connector, comprising: A first circuit component having a first circuit electrode formed on a main surface of a first circuit substrate; A second circuit component having a second circuit electrode formed on a main surface of a second circuit substrate, wherein the second circuit electrode is arranged to face the first circuit electrode; and a connecting component, disposed between the first circuit component and the second circuit component, and electrically connecting the first circuit component and the second circuit component, The connecting member comprises a cured product of the adhesive composition according to any one of claims 1 to 4.

8. The connector according to claim 7, wherein: At least one of the first circuit substrate and the second circuit substrate is a glass substrate.

Citation Information

Cited By

  • Single-sided adhesive-coated PI (Polyimide) film for heating film and preparation method of PI film

    CN121555097A